Is the synthetic stock price really lower than actual price? - HU, Jianfeng (Institutional Knowledge at Singapore Management University, 2020)
Conventional wisdom suggests synthetic stock prices are lower than actual prices due to short‐sale constraints and voting premiums. This study finds that such underpricing of the synthetic midquote disappears if arbitrageurs face security borrowing costs. The synthetic spread predominantly contains the actual spread. Synthetic stock overpricing is as common as underpricing but the former is more persistent and more profitable. The difference between synthetic and actual quotes is significantly affected by options market makers' hedging costs and investors' demand for leverage.